Closed but Not Protected: Excess Deaths Among the Amish and Mennonites During the COVID-19 Pandemic - Stein, Rachel E. (Journal of religion and health, 2021)
“Excess deaths” is a means to estimate the lethality of COVID-19 (directly and indirectly). Assessing “excess death” in closed religious communities provides information on how COVID-19 impacted these communities. We use obituary information published in an Amish/Mennonite newspaper to examine excess death among the Amish/Mennonites in 2020. Our results indicate the Amish/Mennonite excess death rates are similar to the national trends in the USA. The excess death rate for Amish/Mennonites spiked with a 125% increase in November 2020. The impact of COVID-19 on this closed religious community highlights the need to consider religion to stop the spread of COVID-19.